Рейтинг

Оцените: 100% - 1 голосов

100%

алгебра 7 класс

Номер 928

Условие:

Упростите выражение:
а) (у - 3)(у2 + 9)(у + 3)- (2у2 - у)2 - 19;
б) (1 - а)(1 - а2) + (1 + а)(1 + а2) - 2а(1 + а)(а - 1).

 

Ответ:

а) (у - 3)(у2 + 9)(у + 3)- (2у2 - у)2 - 19 = (у2 - 9)(у2 + 9) - (4y4 - 4у3 + у2) - 19 = у4 - 81 - 4у4 + 4y3 - у2 - 19 =
= -3у4 + 4у3 - у2 - 100;

б) (1 - а)(1 - а2) + (1 + а)(1 + а2) - 2а • (1 + а)(а - 1) = 1 - а2 - а + а3 + (1 + a)(1 + а2 - 2а2 + 2а) =
= а3 - а2 - а + 1 + 1 - а2 + 2а + а - а3 + 2а2 = 2а + 2.